Triaging for Severe Illness amongst Adults with Tuberculosis Followed by Referral and Inpatient Care: A Statewide Pilot in Tamil Nadu, India - Hemant D. Shewade; Asha Frederick; Madhanraj Kalyanasundaram; Joshua Chadwick; G Kiruthika; T Daniel Rajasekar; K Gayathri; R Vijayaprabha; R Sabarinathan; Shri Vijay Bala Yogendra Shivakumar; Kathiresan Jeyashree; P K Bhavani; et al. (Preventive Medicine: Research & Reviews)
Background: This research paper reports on the first statewide implementation of differentiated Tuberculosis (TB) care in routine health system settings in India and possibly globally. This pilot aimed to assess the feasibility in routine health system settings and to identify the predictors of triaging and the burden of triage positive. Methods/Design: An observational study involving cross-sectional and longitudinal descriptive design. This differentiated TB care was implemented amongst all public notified adults (≥15 years) with TB (not known to be drug resistant at diagnosis) in routine health system settings involving the existing workforce in Tamil Nadu, India (except Chennai). Results: Of 2,382 adults with TB notified during 14-27 March 2022, 1,636 (69%) were triaged for severe illness and 290 (18%) were triage positive. Of these 298, a total of 160 (55%) were comprehensively assessed after referral. Of 136 confirmed as severely ill, 116 (85%) were admitted and 103 were discharged. The median admission duration was 4 days. From diagnosis, the median time interval to admit a severely ill patient was 1 day. Adults diagnosed by rapid molecular test, with extrapulmonary TB and transferred out of district, were less likely to be triaged. Conclusion: To reduce TB deaths, the losses in the care cascade should be reduced and the admission duration increased. The findings of this pilot exercise guided the eventual implementation starting 01 April 2022.